Guatemala : Selected Issues Paper. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper analyzes remittances and households' behavior in Guatemala. Remittances are a structural feature of the Guatemala economy. In 2017, remittance flows accounted for over 11 percent of GDP and benefitted over 1.5 million of Guatemalan households. The effects of remittances on the labor supply are estimated. There is no evidence of remittance-induced work disincentives. The results suggest that the labor supply for members of remittance-receiving households is relatively more elastic, most markedly so for the 41-65 age group: a one percent increase in weekly wages leads to a 0.5 percent increase in weekly hours worked for members of remittance-receiving households, versus 0.2 percent increase for non-remittance-receiving households.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet